(untitled) (Medical Forum Monthly, 2021)
Objective: The aim of this study was to assess the knowledge, attitude and practice of emergency contraceptive among women who attended Shahida Islam Teaching Hospital Obstetrics and Gynaecology Department in Out Patient department. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at the Shahida Islam Teaching Hospital, Lodhran from April to June, 2018. Materials and Methods: All women of reproductive age, presenting in the gynaecology and obstetrics outpatient department in Shahida Islam Teaching Hospital Lodhran were included in the study. Unmarried, mentally retarded and those who were not willing to participate in survey were excluded. Face to face interview through structured questionnaire was done. Data was collected using structured questionnaire and analyzed using SPSS version 17.0. Descriptive statistics chi-square tests were done and significance of tests was decided at p-value 0.05. Results: In this study 548 women were interviewed. Less than half of them 262(47.8%) were from urban area and 286(52.2%) were from rural area. All of them were married. Of all the respondents 92(16.8%) women had awareness about emergency contraceptive. 82(15%) of the women mentioned pills as emergency contraception and only 26(4.7%) of them mentioned intrauterine device as emergency contraception. 265(48.4%) of them have positive attitude towards emergency contraception but only 64(11.1%) of them have ever used emergency contraceptives. Conclusion: The knowledge and practice of emergency contraception is very low. But there is high positive attitude towards emergency contraceptives. Since there is much deficit on knowledge of women on emergency contraceptives, in addition to making them accessible; programs targeted at promotion and education of emergency contraceptives is helpful to prevent unwanted pregnancy.